2016
DOI: 10.1080/1461670x.2016.1246377
|View full text |Cite
|
Sign up to set email alerts
|

(Un)covering the Economic Crisis?

Abstract: View related articles View Crossmark data Citing articles: 4 View citing articles (UN)COVERING THE ECONOMIC CRISIS? Overtime and inter-media differences in salience and framing Alyt Damstra and Rens Vliegenthart This study takes crisis coverage as the dependent variable. Focusing on the Netherlands, we investigate how print media framed the economic crisis (2007-2013) and to what extent temporal and outlet factors account for variation in the use of frames. Relying on an in-depth qualitative content analysis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Table 1 describes the intervals and related dates. The methodology hereby adopted has been adapted from a study conducted by Damstra and Vliegenthart (2018). 14 For the selection of terms, we created two constructs.…”
Section: How Does the Figurative Framing Of War Change Over Time? Metmentioning
confidence: 99%
“…Table 1 describes the intervals and related dates. The methodology hereby adopted has been adapted from a study conducted by Damstra and Vliegenthart (2018). 14 For the selection of terms, we created two constructs.…”
Section: How Does the Figurative Framing Of War Change Over Time? Metmentioning
confidence: 99%
“…How a certain topic is portrayed in the media affects how the public and decision-makers comprehend and interact with it [ 24 ] Journalists can shape or alter the audience’s perspective of a crisis. Several ways can be applied to do so: the level of attention the reporters devote to the issue, the emotion and tone used in the news coverage, and how the issue is presented through frames [ 25 ]. Since the beginning, the COVID-19 pandemic dominates in major news consumption, and it prompted the President to hold press conferences frequently; but many Americans also depend on their local news outlets to get information regarding the outbreak [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is a social construct and, therefore, often ideologically colored. The vast majority of the economic/financial press tends to support the neoliberal status quo, thereby failing to offer a wider range of other perspectives to the public, most notably perspectives that critically challenge existing capitalistic structures (e.g., Berry, 2012, Berry, 2015, Berry, 2016Chakravartty & Schiller, 2011;Damstra & Vliegenthart, 2016;Davis, 2006, Davis, 2011Doyle, 2006;Durham, 2007;Duval, 2005;Jensen, 1987;Marron, Sarabia-Panol, Sison, Rao, & Niekamp, 2010;Philo, 1995;Philo, Miller, & Happer, 2015;Tambini, 2010;Tracy, 2012). In general, a certain bias in the selection of news stories is inextricably linked to news production processes: (National) cultures, organizational structures, ideological outlet profiles, and differential power of political and societal actors, as well as the choices by individual journalists-all have an impact on the construction of news content (Vliegenthart & Van Zoonen, 2011).…”
Section: Structural Constraintsmentioning
confidence: 99%
“…The financial crisis (2008)(2009)) has served as a fruitful test case for the analysis of existing biases in financial and economic news reporting. Often departing from the question why the media did not see it coming (e.g., Fraser, 2009;Lashmar, 2008;Starkman, 2009), scholars scrutinized the way in which the crisis was covered (Arrese & Vara-Miguel, 2016;Berry, 2012;Damstra & Vliegenthart, 2016;Happer, 2017;Pirie, 2012;Schifferes & Knowles, 2014) in multiple contexts. It is concluded that media covered the crisis rather uncritically, depriving the audience from a diverse array of possible solutions to it (Arrese & Vara-Miguel, 2016;Berry, 2012;Happer, 2017;Mercille, 2013;Pirie, 2012).…”
Section: Structural Constraintsmentioning
confidence: 99%